Impact of increase of caesarean section on postpartum hemorrhage in a tertiary care center of India over 6 years - Madan, Shikha; Sangwan, Neetu; Nanda, Smiti; Sirohiwal, Daya; Dahiya, Pushpa; Singhal, Savita; Arora, Tarun (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: PPH (postpartum hemorrhage) is the leading cause of maternal mortality. Despite of all the medical advancement, maternal mortality rates have declined greatly in the developed world, PPH remains a leading cause of maternal mortality elsewhere. Caesarean section is an obstetric intervention where, normal delivery can pose a risk for mother or foetus. The rate of caesarean section has increased worldwide. A survey conducted by WHO found that the worldwide rate of caesarean section increased from 26.4% between 2004 to 2008, to 31.2% between 2010 to 2011. Methods: We collected data of the caesarean sections and patients who developed PPH over 6 years. We studied the association of temporal increase of caesarean section with PPH. Results: Uterine atonicity continues to be the most common etiology of PPH each year, however, there is an increase in tissue abnormality (retained placenta, placenta praevia, accreta, increta, percreta) over years as there is a significant increase in the incidence of caesarean section. Atonic uterus was the most common cause for obstetric hysterectomies and mortality due to PPH every year. Conclusions: Family planning advise is essential in developing country like ours to counsel patients to prevent multiparity, thus reducing PPH. It is also important to train all the health workers in periphery and referral centers to manage the third stage of labor and atonic uterus to save the mothers. Sagacious attitude towards the decision of caesarean section is needed to prevent maternal morbidity and mortality.